Perspectives from the Survey of Honey Bee Colony Losses During 2015–2016 in Argentina - Requier, Fabrice (2018)
Several countries have carried out surveys of managed honeybee colonies, the results of which suggest high loss rates all over the world. Although Latin America is an important apicultural region, estimates of honeybee colony losses are lacking. This study quantified colony losses in Argentina during the 2015-16 season. Overall, the survey included 28,204 honeybee colonies, of which 15.5% were recorded as lost. The total winter losses (13.0%) were higher than summer losses (3.9%), a result that contrasts with that collected in Uruguay where no seasonality was observed in the 2013-14 losses. Although interesting, such inter-country variability cannot be analysed for Latin America because of the lack of simultaneous and standardized estimates of colony losses. Therefore, we developed a unified questionnaire to simultaneously record colony losses in 10 countries of Latin America in collaboration with 35 researchers. We address the readers of Bee World and ask them to help distribute the questionnaire among potentially interested parties in Latin America.